Characteristics of Precipitation During Meiyu and Huang-Huai Rainy Seasons in Anhui Province of China - Zhou, Yuliang; Zhou, Ping; Zhang, Yuliang; Wu, Chengguo; Jin, Juliang; Cui, Yi; Ning, Shaowei (Frontiers in Earth Science, 2021)
According to the spatial distribution characteristics of the summer monsoon rain-belt, Anhui province was divided into three regions, namely, the south of the Yangtze River region in Anhui Province (SYA), Yangtze-Huai region in Anhui Province (YHA), and the north of Huaihe region in Anhui Province (NHA). The Western Pacific Subtropical High ridge and the number of regional rainy days are adopted to identify the onset and ending dates of Meiyu and Huang-Huai rainy season during 1957-2020, using China’s National Standard “Meiyu monitoring indices”. Then precipitation characteristics of these three regions during Meiyu and Huang-Huai rainy season are investigated. Finally, the return periods of the precipitation during the northward move of summer monsoon over Anhui Province are calculated. The results show that there are 7 years without the occurrence of Huang-Huai rainy season, but 8 years with the occurrence of two Meiyu periods and 5 years with two Huang-Huai rainy periods. Thus, there is only one Meiyu period and one Huang-Huai rainy period in the rest 49 years. For the first Meiyu period during 1957-2020, the average onset and ending dates are specified as 14th June and 10th July, respectively, while the corresponding precipitation presents a decreasing tendency from south to north regions in Anhui Province. For the first Huang-Huai rainy period during 1957-2020, the average onset and ending dates are 10th July and 23rd July, respectively, and the corresponding precipitation shows an increasing tendency from south to north regions. For the northward move of summer monsoon over Anhui Province, the average onset and ending dates are 14th June and 25th July, respectively, and the corresponding precipitation in NHA is close to that in YHA, but less than that in SYA. Annual precipitation in SYA, YHA, NHA are 999.5 mm, 1010.6 mm, 618.7 mm during the northward move of summer monsoon over Anhui Province in 2020, and the corresponding return periods are 56.0, 161.6, and 29.2 years respectively.